Response of Pearl Millet to Azospirillum as Influenced By N Fertilizer Under Field Conditions - Joshi, N L; Rao, A V (Annals of Arid Zone, 2016)
Response of pearl millet to inoculation with Azospirillum brasilense. in conjunction with nitrogen application, was studied under field conditions. There was an increase of 37.9% in tillers, 44.3% in heads and 31.2% in test weight upon inoculation. Inoculation effect was reduced with increase in N application. Azospirillllm inoculation resulted in enhanced N2-ase activity and root dry weight. The population of Azospirillium in the roots of inoculated plants was higher as compared to uninoculated once. The inoculation response on grain yield was equivalent to about 13 kg N oa-1•